Statefinder Diagnostic for Variable Modified Chaplygin Gas in LRS Bianchi Type I Universe - K. S. Adhav (Advances in Mathematical Physics)
The Locally Rotationally Symmetric (LRS) Bianchi type I cosmological model with variable modified Chaplygin gas having the equation of state 𝑝=𝐴𝜌−𝐵/𝜌𝛼, where 0≤𝛼≤1, 𝐴 is a positive constant, and 𝐵 is a positive function of the average-scale factor 𝑎(𝑡) of the universe (i.e., 𝐵=𝐵(𝑎)) has been studied. It is shown that the equation of state of the variable modified Chaplygin gas interpolates from radiation-dominated era to quintessence-dominated era. The statefinder diagnostic pair (i.e., {𝑟,𝑠} parameter) is adopted to characterize different phases of the universe.